Stochastic Optimization of Supply Chain Risk Measures –a Methodology for Improving Supply Security of Subsidized Fuel Oil in Indonesia - Yuanita, Adinda; Sommeng, Andi Noorsaman; Wijonarko, Anondho (Makara Journal of Technology, 2015)
Monte Carlo simulation-based methods for stochastic optimization of risk measures is required to solve complex problems in supply security of subsidized fuel oil in Indonesia. In order to overcome constraints in distribution of subsidized fuel in Indonesia, which has the fourth largest population in the world—more than 250,000,000 people with 66.5% of productive population, and has more than 17,000 islands with its population centered around the nation's capital only—it is necessary to have a measurable and integrated risk analysis with monitoring system for the purpose of supply security of subsidized fuel. In consideration of this complex issue, uncertainty and probability heavily affected this research. Therefore, this research did the Monte Carlo sampling-based stochastic simulation optimization with the state-of-the-art "FIRST" parameter combined with the Sensitivity Analysis to determine the priority of integrated risk mitigation handling so that the implication of the new model design from this research may give faster risk mitigation time. The results of the research identified innovative ideas of risk based audit on supply chain risk management and new FIRST (Fairness, Independence, Reliable, Sustainable, Transparent) parameters on risk measures. In addition to that, the integration of risk analysis confirmed the innovative level of priority on sensitivity analysis. Moreover, the findings showed that the new risk mitigation time was 60% faster than the original risk mitigation time.